The Effect of Aaerobic Exercise on Functional Capacity Increase in Coronary Heart Disease Patients: A Narrative Review - Khairullah, Rahmad Rizaldy; Norlinta, Siti Nadhir Ollin (Universitas Muhammadiyah Surakarta, 2023)
The heart condition known as coronary heart disease (CHD) is brought on by the narrowing of the coronary arteries as a result of atherosclerosis, spasm, or a combination of both. This results in a disruption in the supply of oxygen and nutrients to the myocardial tissue due to a decrease in coronary blood flow and a reduction in functional capacity. Objective: The study aims to determine the effect of aerobic exercise on functional capacity increase in coronary heart disease patients. Method: The research employed a narrative review method with the PICO framework (Population/Patient/Problem, Intervention, Comparation, and Outcome). The journals were searched from 2 databases, namely Google Scholar with 15,700 articles and Pubmed 639 articles. The inclusion criteria in this study were national or international articles and full text about the effect of aerobic exercise on functional capacity decline in coronary heart patients published in 2012- 2022. Result: After reviewing the title, relevancy of the abstract, and full text of 16,334 papers from 2 databases, 10 journals demonstrated that aerobic exercise was effective to increase the functional capacity in coronary heart disease patients. Conclusion: There is an effect of aerobic exercise on functional capacity increase in coronary heart disease patients. Keywords: Aerobic Exercise, Coronary Heart Disease, Functional Capacity